PENGARUH PARTISIPASI ANGGARAN DAN TEKNOLOGI INFORMASI TERHADAP KINERJA MANAJERIAL - Yunita, Eka Nur; Sabaruddinsah, Sabaruddinsah (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2011)
This study aims to examine the effect of budgetary participation and influence of information technology on managerial performance (empirical studies on manufacturing companies in bogor). Research method used is survey method by using the respondent managers working in manufacturing companies in bogor, amounting to 81 respondents. Based on the results can be concluded that budgetary participation has a positive and significant impact on managerial performance, as shown by the b1 value of 0,212 with a positive direction and significant value, to the then information technology has a positive and significant impact on managerial performance, this is indicated by the value b2 amounted to 0,422 with a positive direction and significant value, further budgetary participation and interaction of information technology has a positive and significant impact on managerial performance, this is indicated with a value of b1 is 0,215 and b2 is 0,427 with a positive direction.